Pengaruh Capital Adequacy Ratio dan Financing to Deposit Ratio terhadap Laba Bank Umum Syariah - Laurentia, Paula; Lindrawati, . (Widya Mandala Surabaya Catholic University, 2010)
This research is intended to knowing the effect of capital adequacy ratio and financing to deposit ratio on syariah bank net income. If bank have good capital adequacy ratio and financing to deposit ratio, bank could financing and operating their activities with well so it could increase their net income. Multiple regression analysis is used as a research method, which contains of classic assumption test and hypothesis test (F-test and t-test). Based on the regression result, it is found that hypothesis test shows that capital adequacy ratio and financing to deposit ratio have effect on syariah bank net income.